Dual Application of Ethephon and DCPTA Increases Maize Yield and Stalk Strength. (1st March 2019) - Li, L.L.; Gu, W.R.; Li, C.F.; Li, W.H.; Chen, X.C.; Zhang, L.G.; Wei, S.
Abstract : Core Ideas: Combined treatment with ethephon and DCPTA enhanced stalk mechanical strength of maize. Combined treatment with ethephon and DCPTA improved the post‐anthesis dry matter accumulation of maize. Combined treatment with ethephon and DCPTA improved the grain yield of maize. The combination of ethephon (2‐chloroethyl phosphonic acid, ETH) and 2‐diethylaminoethyl‐3, 4‐dichlorophenylether (DCPTA) has been used in maize ( Zea mays L.) production in Northeast China, but limited information is available on the effectiveness of ETH+DCPTA. In this study, field experiments were conducted with two maize hybrids, ZhengDan 958 ('ZD958') and DongNong 254 ('DN254'), which were planted at a density of 75, 000 plants ha −1, to study the influence of ETH, DCPTA, and ETH+DCPTA on stalk quality (rind penetration strength [RPS], stalk bending strength [SBS], dry weight per unit, cross‐sectional area, and rind thickness), photosynthetic characteristics, bleeding sap, dry matter accumulation (DMA), and yield. Ethephon significantly reduced the lodging rate, plant height, ear height, and center of gravity of both maize hybrids and increased the RPS, SBS, dry weight per unit, cross‐sectional area, and thickness over the 2 yr. Ethephon also significantly decreased the leaf area index (LAI), chlorophyll content (SPAD value), net photosynthetic rate (Pn ) and bleeding sap levels and accelerated leaf senescence, which ultimately decreased the yields. Although the application of DCPTA tended to increase the LAI, Pn, and bleeding sap levels and delayed leaf senescence, the plant height, ear height and the center of gravity also increased markedly, resulting in poorer stalk lodging resistance and higher lodging rate. Greater green leaf area, photosynthetic ability and bleeding sap levels and delayed leaf senescence in response to ETH+DCPTA mainly contributed to the increased postanthesis DMA. Thus, the application of ETH+DCPTA could provide a stable method for increasing the maize grain yield.